EPB: A SCALE FOR EVALUATING THE PROFESSIONAL BURNOUT - García Izquierdo, Mariano; P. Velandrino, Antonio (Anales de Psicología / Annals of Psychology)
The burnout is a term variouslly defined. It can mean, at the starting, an illness resulting from big and continous efforts at work. The MBI (Maslach Burnout Inventory) is a very generalized scale to evaluate the level of burnout. It presents three dimensions to be related to burnout term: exhaustion, despersonalization and negative personal acomplishment. Recent works, nevertheless, point out the first of them as the most appropiate. In this paper we have developped a new scale focused in the first dimension and our social and cultural context: the EPB (Escala para la Evaluación del Burnout Profesional). Early psychometrics analyses support the fitness to concept burnout more currently accepted.